PARTITION BEHAVIOUR OF ALKYLPHENOLS IN CRUDE OIL/BRINE SYSTEMS UNDER SUBSURFACE CONDITIONS - Bennett B.; Larter S.R. (My University, 1997)
Partition of organic solutes between oils and water in the subsurface is an important geochemical process occurring during petroleum migration and reservoiring, during water washing, and during petroleum production. Currently no data exists on the quantitative aspects of the partition process at subsurface conditions for solutes such as phenols and aromatic hydrocarbons which are major components of both oils and waters. We have constructed an equilibration device for oils and waters based on flow injection analysis principles to measure partition coefficients of alkylphenols in crude oil/brine systems under reservoir conditions. Concentrations of C0-C2 alkylphenols in waters and solid phase extracts of crude oils produced in the device were determined by reverse phase high performance liquid chromatography with electrochemical detection (RP-HPLC-ED), partition coefficients being measured as a function of pressure (25-340 bar), temperature (25-150°C), and water salinity (0-100,000 mg/L sodium chloride) for a variety of oils. Partition coefficients for all compounds decreased with increasing temperature, increased with water salinity and crude oil bulk NSO content, and showed little change with varying pressure. These laboratory measurements, determined under conditions close to those typically encountered in petroleum reservoirs, suggest temperature, water salinity, and crude oil bulk NSO content will have important influence on oil-water partition processes in the subsurface during migration and water washing.